GROWTH-STIMULATING EFFECT OF BACILLUS THURINGIENSIS DELTA-ENDOTOXIN ON WHEAT AND BARLEY GROWN IN UZBEKISTAN (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study investigates the effect of Bacillus thuringiensis delta-endotoxin on the development of wheat (Andijan-2 variety) and barley (Ikhtiyor variety). The experiment was conducted using different concentrations of delta-endotoxin to determine its impact on seed germination energy and germination rate. The optimal concentration (0.7%) increased germination energy by 18% and laboratory germination by 15% compared to control samples. It was found that the application of delta-endotoxin stimulates the synthesis of heteroauxin and ascorbic acid, positively affecting the biometric characteristics of seedlings. Specifically, root length increased by 43.2%, stem length by 75%, seedling mass by 45-56%, and stem diameter by 55-60%. The identified growth-stimulating effect is due to both the direct impact of endotoxin on plants and its protective effect against phytopathogens. The obtained results can be used for the development of biopreparations aimed at increasing the productivity of agricultural crops.